On the existence and uniqueness of solutions continuous and bounded on the real axis for nonlinear functional equations - Pelyukh, G. P. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
For one class of nonlinear functional equations, we establish conditions for the existence and uniqueness of solutions continuous and bounded on the real axis.